Confinement Effect and Hydrogen Species Modulation toward Enhanced Electrochemical CO2 Reduction to Ethanol - Yuting Zhu; Jiamin Zhu; Huizhi Li; Shuhui Li; Yue Zhai; Shao-Wen Xu; Shanshan Wu; Yuan Chen; Yafu Wang; Rui Ren; Li An; Jiangwei Zhang; et al. (Research, 2025)
The protonation process of adsorbed *CO intermediates has been widely recognized as a critical determinant governing product selectivity in electrocatalytic carbon dioxide reduction reaction (eCO2RR). However, the active hydrogen species and mechanism of *CO protonation in acid eCO2RR remain ambiguous. Particularly, the involvement of H+ in *CO hydrogenation is still under debate. Here, we developed a CuCl-mediated synthesis strategy integrated with rare-earth doping electronic structure engineering, which enriches intermediates and promotes adsorbed hydrogen (*H) participation in reactions, respectively. For the first time, differential electrochemical mass spectrometry (DEMS) and nuclear magnetic resonance (NMR) were employed to clarify the participation of hydrogen species in liquid and gaseous eCO2RR products, with isotope labeling utilized to distinguish the distribution of H+ and *H in the products. Experimental verification confirmed that in acidic electrolytes, the ethylene pathway was dominated by H+ hydrogenation, whereas the ethanol pathway incorporated contributions from both H+ and *H. Upon yttrium (Y) doping into Cu2O/CuCl, interfacial water activation was markedly enhanced, thereby enabling the provision of supplementary *H for catalytic engagement. Notably, our Y-Cu2O/CuCl catalyst achieves a remarkable 65.7% Faradaic efficiency for ethanol with exceptional 65-h stability at 200 mA cm−1. This work provides new evidence for H+ participation in acid eCO2RR, emphasizing the critical role of H2O activation degree in selectivity regulation, and thus offering novel insights for designing efficient acid eCO2RR catalysts.